(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Sesame plant (sesamum indicum Lin.) Belonging to family Pedaliaceae. Sesame seed oil also known as queen of oil which contains number of phytochemicals like thiamine, riboflavin, niacin, pyridoxine, folic acid, vitamin B12, ascorbic acid, stearic acid, linoleic acid, palmitic acid and Various lignance like sesamolin, pinoresinol, sesamin, Sesamol, tocopherols which are potent antioxidants and has reported neuroprotective action therefore, Sesame seed oil (SSO) was used in present study to investigate its protective action on chlorpromazine (CPZ) associated extrapyramidal side effects (EPSE) in animal model. The study was designed by giving CPZ (3mg/kg ip) for 21days to induce EPSE in animals. CPZ significantly induce EPSE (Catalepsy, muscular rigidity and hypolocomotion) in a period of 21 days. The effect of SSO on CPZ induced EPSE in rat was evaluated using doses 200mg/kg and 400mg/kg PO. Syndopa (10mg/kg) was used as standard drug. During 21 days of study animals behavioral parameters were evaluated after each 7 days of interval by block test (catalepsy), Rotarod test (muscular rigidity) and Actophotometre (locomotors activity). Animals showed significantly reduced catalepsy score, increased fall of time and increased locomotors activity in dose dependant manner. Biochemical estimation of dopamine (DA) and antioxidant parameters were also evaluated. SSO treated animal groups showed significant increase in level of DA, Catalase and reduced glutathione preferably at higher dose. Thus present study validates that SSO has an antioxidant and protective effect on CPZ associated EPSE.